Heat transfer enhancement in natural convection in micropolar nanofluids - Rup, K.; Nering, K. (Archives of Mechanics, 2016)
In this work an analysis of momentum, angular momentum and heat transfer during unsteady natural convection in micropolar nanofluids is presented. Selected nanofluids treated as single phase fluids, contain small particles. In particular, two ethylene glycol-based nanofluids were analyzed. The volume fraction of these solutions was 6%, 3.5% and 0.6%. The first ethylene glycol solution contained Al2O3 nanoparticles (d = 38.4 nm), and the second ethylene glycol solution contained Cu nanoparticles (d = 10 nm).